HERDING BEHAVIOR IN THE INDONESIAN ISLAMIC STOCK MARKET - Nora Amelda Rizal; Mirta Kartika Damayanti (Journal of Islamic Monetary Economics and Finance, 2019)
Indonesia Stock Exchange provides Islamic stocks for Muslim investors who want to invest, with the first Islamic stock index in Indonesia being Jakarta Islamic Index or JII that consists of thirty of the most liquid Islamic stocks. The market capitalization of JII tends to increase every year. This paper examines the presence of herding behavior in emerging Islamic stock market of Indonesia using daily return of Indonesia Composite Index and JII from October 6, 2000 to October 5, 2018. Herding behavior could generally trigger shifting market prices from equilibrium values. Herding behavior may be identified from the relation between stock return dispersion and market return. Stock return dispersion is measured using Cross Sectional Absolute Deviation or CSAD. Generalized Auto Regressive Conditional Heteroskedasticity or GARCH method is used to detect herding behavior. GARCH does not see heteroskedasticity as a problem, instead uses it to make a model. The result indicates that herding behavior exist in Islamic stock market of Indonesia. Asymmetric herding occurs in Indonesia Islamic stock market where herding behavior exists during falling market condition only.